Conservation of intraoral pressure changes during swallowing - Chris Bolter; Nitin Raniga; J. Neil Waddell; Jules Kieser (Elsevier, 2012)
Background/purpose: A relationship between malocclusion and intraoral pressure is suspected but ill understood. This study explores intra-oral pressure changes during normal swallowing to assess differences in patterns of command saliva and water swallows. Materials and methods: We used a custom-made appliance fitted with miniature pressure transducers located along the midline at the anterior-, mid-, and hind palate to measure absolute pressures during command water and saliva swallows. Data were obtained from eight healthy volunteers (six males, two females; 24-35 years) with full permanent dentitions. Following accommodation, volunteers performed 10 mL water and saliva swallows on command. Each volunteer performed the swallows three times on 5 separate days, yielding data from 15 swallows for each individual. Results: Each participant had a distinct pressure response during swallowing. At all three locations, negative pressure amplitude was greater than positive pressure amplitude, with no significant difference between swallowing saliva and water. There was a larger rate of negative pressure development (P < 0.01) and a larger value for the pressure-time integral (P < 0.05) at the front of the palate during water swallowing. During water swallowing, the root mean square pressure integral (index of work) at the front of the mouth was larger (P < 0.05), and there was a significant front to mid palate pressure gradient (P < 0.05) that was not evident during saliva swallowing. Conclusion: We tested the hypothesis that a liquid with a low viscosity (water) requires less lingual propulsive deformation than a higher viscosity liquid such as saliva. Although saliva is a more complex fluid than water and varies between individuals, participants produced personally distinct and consistent signature pressure patterns and retained these for both liquids.